Desain dan Analisis Struktur Baja Gudang Perlengkapan Tambahan Bandar Udara Hang Nadim dengan Metode LRFD - Darmawan, Muhammad Zhabri Gaffari (aspal, 2025)
Warehouse facilities at airports are essential infrastructure that support aviation operations, particularly as storage areas for materials, equipment, and supplies required by technical units. Based on field observations at Hang Nadim International Airport, it was identified that the equipment building has reached its maximum capacity, resulting in suboptimal organization of operational items and a potential decline in storage quality. To address this issue, an additional warehouse is planned to be constructed behind the existing equipment building in order to increase storage capacity and ensure that items remain properly maintained. This study aims to analyze and design the steel structure for the additional warehouse using the Load and Resistance Factor Design (LRFD) method. The calculation results indicate that the warehouse structure is designed using several steel profiles, including WF 300×150×6.5×9 for columns, WF 250×125×6×9 for long-span rafters, WF 200×100×5.5×8 for beams, and WF 150×75×5×7 for medium-span rafters. In addition, A325-grade bolts with diameters ranging from 16 to 20 mm are used for the main connection points. Based on the structural design, the warehouse meets the required strength criteria; however, further geotechnical analysis is needed to produce a more comprehensive and reliable warehouse design.